2000
DOI: 10.1097/00002093-200004000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Telemedicine System As a Care Modality for Dementia Patients in Korea

Abstract: Because dementia is a chronic debilitating disease, there are the issues of the difficulty in continuous long-term care and limited accessibility to medical service. We developed the telemedicine system for dementia patients and aimed to examine the acceptance, reliability, and clinical outcome of our telemedicine service. We established the Dementia Telemedicine Center in connection with two recipient sites in 1996. The reliability of the center, which provides telemedicine, tele-education, and telecounseling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 21 publications
0
75
0
8
Order By: Relevance
“…In addition, formal caregivers were participating in studies in which information and communication technologies (ICT) were used for their own education (Calleson, Sloane, & Cohen, 2006;Engström, Ljunggren, Lindqvist, & Carlsson, 2005;Lyketsos, Roques, Hovanec, & Jones, 2001;Poon, Hui, Dai, Kwok, & Woo, 2005) or to improve access to diagnosis (Cullum, Weiner, Gehrmann, & Hynan, 2006;Gatz et al, 2002;Larner, 2003;Lee et al, 2000, Mundt, Moore, & Greist, 2005. Changing the indoor environment of the residential care by hiding doors or by using lines Topo / Needs of People With Dementia and Their Caregivers 11 or bars on floor or door patters showed no success in stopping the wandering of people with dementia in these studies (Dickinson et al, 1995;Feliciano et al, 2004;Hewawasam, 1996), but they suggested that ICT can be used more effectively in providing information and education on dementia in delivering diagnostic (Cullum et al, 2006;Gatz et al, 2002;Larner, 2003;Lee et al, 2000) and support services, in integrating the residents and the residential care in society, and in providing meaningful activities for them (Baker et al, 1997;Burgio et al, 1996;Camberg et al, 1999;Lucero et al, 2000;McConatha et al, 1994;Tamura et al, 2004). In addition, there were 15 studies in which formal caregivers were one of the user groups and the studies aimed at providing technology-mediated support services for family carers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, formal caregivers were participating in studies in which information and communication technologies (ICT) were used for their own education (Calleson, Sloane, & Cohen, 2006;Engström, Ljunggren, Lindqvist, & Carlsson, 2005;Lyketsos, Roques, Hovanec, & Jones, 2001;Poon, Hui, Dai, Kwok, & Woo, 2005) or to improve access to diagnosis (Cullum, Weiner, Gehrmann, & Hynan, 2006;Gatz et al, 2002;Larner, 2003;Lee et al, 2000, Mundt, Moore, & Greist, 2005. Changing the indoor environment of the residential care by hiding doors or by using lines Topo / Needs of People With Dementia and Their Caregivers 11 or bars on floor or door patters showed no success in stopping the wandering of people with dementia in these studies (Dickinson et al, 1995;Feliciano et al, 2004;Hewawasam, 1996), but they suggested that ICT can be used more effectively in providing information and education on dementia in delivering diagnostic (Cullum et al, 2006;Gatz et al, 2002;Larner, 2003;Lee et al, 2000) and support services, in integrating the residents and the residential care in society, and in providing meaningful activities for them (Baker et al, 1997;Burgio et al, 1996;Camberg et al, 1999;Lucero et al, 2000;McConatha et al, 1994;Tamura et al, 2004). In addition, there were 15 studies in which formal caregivers were one of the user groups and the studies aimed at providing technology-mediated support services for family carers.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have been performed regarding the use of telemedicine in patients with dementia. One study (Lee et al, 2000) found that staff and patients at a dementia unit were satisfied with telemedicine consultative services. Another study (Lyketsos et al, 2001) found that a geriatric telemedicine service in a dementia unit decreased acute hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these activities were combined with traditional home health caring strategies. 30,31 Teleconsultations between the nurse specialists located at a veterans clinic and a multidisciplinary wound care team were also reported. 9 The second large category dealt with telemonitoring.…”
Section: Publication Contentmentioning
confidence: 99%